Помогите, прошу!

0 голосов
54 просмотров

Помогите, прошу!
\sqrt[3]{8x + 4} - \sqrt[3]{8x - 4} = 2


Алгебра (224 баллов) | 54 просмотров
Дан 1 ответ
0 голосов
\sqrt[3]{8x+4}=2+ \sqrt[3]{8x-4} \\ 8x+4=(2+ \sqrt[3]{8x-4})^3
8x+4=8+6 \sqrt[3]{(8x-4)^2}+12 \sqrt[3]{8x-4}+8x-4
сокращаем подобные
6 \sqrt[3]{(8x-4)^3}+12 \sqrt[3]{8x-4} =0
\sqrt[3]{(8x-4)^2}+2 \sqrt[3]{8x-4}=0
Делаем замену y= \sqrt[3]{8x-4}
y²+2y=0
y(y+2)=0
y1=0
y2=-2
Подставляем
\sqrt[3]{8x-4}=0 \\ 8x-4=0 \\ 8x=4 \\ x=1/2
\sqrt[3]{8x-4} =-2 \\ 8x-4=-8 \\ 8x=-4 \\ x=-1/2
Ответ: х=+/-1/2
(2.9k баллов)